Ribosome Role in Regulating Concurrency of mRNA Translation - H. Costa Neto, Luis; Lifschitz, Sérgio; Catanho, Marcos; B. de Miranda, Antônio; Haeusler, Edward H. (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
mRNA translation involves complex concurrent processes in which many mRNA strands might be processed simultaneously, leading to parallel consumption of potentially scarce resources. Previous studies have shown that excess mRNA can harm protein synthesis efficiency. This work investigates the role of ribosomes as concurrency controllers in regulating translation dynamics. Using Petri net modeling, we demonstrate that ribosomes act as natural regulators that limit the detrimental effects of mRNA abundance by controlling the number of concurrent translation events. Our experimental results show ribosome availability is a protective mechanism against greedy consumption patterns that lead to incomplete protein synthesis. This finding provides insights into the regulatory mechanisms maintaining translation efficiency in cellular systems.